Penggunaan media let’s read (ayo membaca) untuk meningkatkan kemampuan menceritakan kembali isi cerita peserta didik kelas III sekolah dasar - Utami, Widya Pangesti; Ardiansyah, Roy (Universitas Sebelas Maret, 2025)
This research focuses on illustrating the enhancement of storytelling skills through the implementation use of Let's Read media in younger grades. The study utilized Classroom Action Research (PTK) with a framework based on the Kemmis and McTaggart model, executed in two distinct cycles. Each cycle comprised stages of planning, implementation, action, observation, and reflection. The subjects involved were 22 third grade students from SDN Dukuhan Kerten, including 6 boys and 16 girls. Various methods for data collection were employed, including observation, interviews, storytelling assessments, and documentation. To ensure validity, both source and method triangulation were applied. Findings revealed that the use of Let’s Read media led to improvements in students' ability to recount stories across both cycles. In the first cycle, the enhancement was 68.4%, equating to 13 students, while the second cycle saw a rise of 89.4%, involving 17 students. This progress was evident in storytelling skills as student demonstrated coherent narration, fluent delivery, appropriate intonation, correct expressions, and accurate pronunciation.